Effect of structural ideotypes on yield attributes, seed yield and their inheritance in Yellow Sarson (Brassica rapa L. var. Yellow Sarson) - Ram Babu Raman; SP Sinhamahapatra (Journal of Oilseed Brassica, 2026)
The experiments were conducted in three replications for two consecutive years at Instructional Farm Jaguli, BidhanChandra Krishi Viswavidyalaya, Mohanpur, West Bengal. The different plant ideotypes (Waxy petalous, waxy apetalous,nonwaxy petalous and nonwaxy apetalous) of Brassica rapa var Yellow Sarson were studied during the investigation.Four ideotypic groups showed significant variation for most of the traits in both the years. Waxy apetalous grouprecorded highest mean values for most of the traits including seed yield per plant in two consecutive years whereasNonwaxy petalous groups recorded lower seed yield, 1000 seed weight and plant height. In waxy apetalous group, seedyield per plant showed significantly positive correlations with plant height, number of primary branches, number ofsiliquae per plant, number of seeds per siliqua and 1000 seed weight while in waxy petalous group, seed yield per plantshowed significantly positive correlations with number of primary branches, number of seeds per siliqua, and 1000 seedweight. In nonwaxy apetalous group, seed yield per plant showed positive correlations with number of primary branchesand number of siliquae per plant. In nonwaxy petalous group, seed yield per plant showed significantly positivecorrelation with number of primary branches, number of seeds per siliqua and hundred seed weight.